Music Performance Encounters: Collaborations and Confrontations - Koslovsky, John; Schuijer, Michiel (Abingdon, Oxon New York Routledge, 2023)
"Why do most musical performers and musical researchers continue to inhabit divergent epistemic spaces? To what extent is the act of musical performance coextensive with the act of doing musical research, and vice versa? At what point in the research process can a performative act transform into a scholarly one, and a scholarly act into performative one? These, and other related questions, form the central focus of this book with each chapter offering a fresh perspective on a particular topic in music performance studies: improvisational traditions, historical performance practices, analysis and performance, sports psychology, cross-cultural musical interactions, and institutional challenges. This book is aimed at music researchers, teachers, students, and practicing musicians interested in the intersection of academic and performance research and bridges the divide between the research of university-trained musicologists, scholars from other fields who focus on music, and the growing community of musical artist-researchers. Material in the book is supported by performance outcomes offered by the contributors on a separate YouTube channel and on the Routledge online portal"--
Introduction. "Who Are You?" : On Performers, Scholars, Masters, and Pupils / Michiel Schuijer and John Koslovsky -- Critical Interlude 1 / John Koslovsky -- Part I. Tools of (Historical) Performance Practice. "Che hanno contrapunto" : Counterpoint Training and the Performance of Diminution in the Sixteenth and Seventeenth Centuries / Catherine Motuz and Josué Meléndez ; The Italian Imitative and Interdisciplinary Musical Ethos of the Sixteenth Century : Ganassi's La Fontegara / Nuno Atalaia and Tímea Nagy ; Echos of Cor Alto and Cor Basse : In Search of an Ideal Horn Sound / Kathryn Zevenbergen and Teunis van der Zwart -- Critical Interlude 2 / John Koslovsky -- Part II. Scholars and Performers in Dialogue. Analysing and Playing Chopin's Nocturne Op. 27, no. 1 : An Empirical Study of the Interaction between Analysts and Performers / Luca Marconi and Stefano Malferrari ; Resonant Openings : Collaborating on Crumb's Nocturnes / Michiko Theurer and Daphne Leong -- Critical Interlude 3 / Michiel Schuijer -- Part III. Institutional Endeavours. The Absent Teacher Approach / Job ter Haar, Michalis Cholevas and Juliano Abramovay ; Preparing Music Students for a Public Recital : Applying Principles of Practice from Sport Sciences and Other Disciplines / Frank C. Bakker, Jan Kouwenhoven, Valle González Martín and Raôul R.D. Oudejans -- Critical Interlude 4 / Michiel Schuijer -- Part IV. Cultural Barriers and Embodied Knowledge. Knowing the World through Music / Barbara Titus, Shishani Vranckx and Bart Fermie ; Performing Jennifer Walshe's SELF-CARE / Andreas Borregaard.
Includes bibliographical references and index.
Keywords: Historically informed performance; Musical analysis; Music psychology; Teaching